KOMODIFIKASI HIJAB DALAM IKLAN SAMPO SUNSILK HIJAB RECHARGE - Iis Mariati; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The development of hijab in Indonesia is growing from time to time aimed at increasing numbers of Indonesian women wearing hijabs. Now hijab is very popular among Muslim women in Indonesia, now the hijab is not considered ancient, now hijab and Muslim clothing actually make women who wear it look more beautiful and graceful and more fashionable. At present the style of hijab displayed by Muslim women is starting to be highlighted by the media, so employers are starting to see this gap to take the opportunity to advertise their products using hijab women to be more quickly recognized by the public. In this study, researchers analyzed the Sunsilk Hijab Recharge advertisement, where advertising stars used hijab as an attribute of religious value in the advertising value, and religious values (hijab) in these advertisements became a commodity. So that there was a transfer of the function of religious values into an exchange rate. Utilization of hijab from its use which is then transformed into a commodity and certain interests.This research method uses Charles Sanders Peirce's semiotic analysis. The data collection technique carried out is through observation and documentation. The data validity technique in this research is triagulation.The results of this study indicate that the commodification that appears in the Sunsilk Hijab Recharge Sampo advertisement is the commodification of content seen from the signs and meanings of the description of the story. The use of commodified hijab causes the ad to experience a shift from function value to exchange rate. A company and the interests of making advertisements to get people to use Sunsilk Hijab Recharge shampoo products through the use of visual religious signs is an absolute means to get empathy and sympathy from the public to buy and use these products. The researcher realizes that the sign is a concept to promote the product so that it becomes a commodity and functions to become a function of selling in the form of capitalism.Keyword : Comodification Hijab, Semiotics Charles Sanders Pierce